SEBUAH MODEL PEMROGRAMAN BILANGAN BULAT UNTUK PENYELESAIAN MASALAH PENJADWALAN SUMBER MAJEMUK PARALEL SIMULTAN - Parwadi Moengin; Felia Indah Kusuma (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Manufacturing company engaged in textile manufacturing in the Job Order system with an extensive network and market orientation requires more attention to the quality of products and services that meet customer requirements, one of them by way of the fulfillment of an order at the time agreed in advance. The problems are often found in the companies are delays in the completion of orders. This is due to less optimal job scheduling order by weight or penalty different on each job which will ultimately lead to the total weighted delay of the delay comes from the accumulation of a different job with the weights. This paper is intended to help companies create a new and more optimal scheduling in order to minimize the total weighted delay in the completion of order.The model used in this paper is an integer linear programming model for resource-scheduling problem for multiple simultaneous parallel job-compound and compound-operation. The initial steps of the use of this model is the formulation of the decision variables, and the objective function is minimizing total weighted tardiness or delay subject to the limiting functions. Software used in the processing of this data is WinQSB. At the end of the text is given a numerical example using the proposed model.